PENGARUH PENDIDIKAN KESEHATAN DENGAN METODE ULAR TANGGA TERHADAP PENGETAHUAN ANAK USIA SEKOLAH TENTANG MAKANAN SEHAT DI PANTI ASUHAN KEMULIAAN PASIR PUTIH PEKANBARU - Dwi Elka Fitri; Lince Kartika Jelita Laia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The food consumed by school children greatly affects their physical development. Lack of consuming healthy food in school-age children can cause disease or impaired growth and development in later life. So the strategy is to provide education about healthy food. The purpose of this study was to determine whether there is an effect of health education with the snake and ladder method on the knowledge of school-age children about healthy food. Respondents in this study were 32 respondents. This study uses a pre-experimental research design in the form of a